Ovarial function in pts with systemic lupus erythematosus - S Sh Sliabanova; Z S Alekberova; I I Guzov; L P Ananyeva (Научно-практическая ревматология)
Objective. To assess ovarian function and its changes during therapy with cyclophosphan (CPh) in pts with systemic lupus erythematosus (SLE). Material and Methods. 44 pts with SLE aged 16 to 45 years with intact menstrual cycle were examined. 18 from them had received CPh earlier (mean cumulative dose 5,7 g), 26 had been never treated with CPh. Mean age, disease duration and activity (according to SLEDAI) as well as glucocorticoid (GC) doses were similar in both groups. Blood sex hormones - follicle-stimulating hormone (FSH), lutropin (LT), prolactin, estradiol, progesterone were tested with immune-enzyme assay. Each pt was examined by a gynaecologist, pelvis minor ultrasonography was performed, basal temperature was measured during 3 months Results. CPh treated pts had lower mean progesterone levels but higher FSH and LT than pts that had not received CPh. Intensity of these changes depended on cumulative dose of CPh and age of pts. Failure of menstrual cycle lutein phase was found with similar frequency in both groups and achieved in average 63%. Oligomenorrhea and more than twofold menstrual cycle shortening were present more frequently in pts treated with CPh (p<0,05). Conclusion. Treatment with CPh increase risk of ovarian dysfunction in pts with SLE. Failure of menstrual cycle lutein phase does not exclude autoimmune genesis of oophoritis in SLE.